1997
DOI: 10.1111/j.1439-0426.1997.tb00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Food selection and growth of young snakehead Channa striatus

Abstract: Food selection and growth of young snakehead Chunnu striutus were studied in the laboratory and in a field trial. In the laboratory, first-feeding snakehead larvae of 6-7 mm total length (TL) with a mouth opening of 0.55 mm sclectcd for Arteniiu nauplii, and against formulated feed. Fish began feeding on kormulated feed at 12mm T L when their mouth width reached 1 .0mni. In both laboratory and field trials, snakehead diets changed as fish size increased. For fish 15-20 mni TL, cladocerans and copepods were 96.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 17 publications
1
25
0
2
Order By: Relevance
“…Snakeheads of the genus Channa include several carnivorous species that possess high economic value and are widely recognized as staple food fish (Courtenay and Williams, 2004;Qin and Fast, 2007;Sampath, 1984;Sampath and Pandian, 1984;Wee, 1982). In addition, snakeheads are used as ornamental fish in aquariums and their consumption is considered therapeutic for wound healing after trauma and surgical procedures including, Cesarean sections (Benziger et al, 2011;Gam et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Snakeheads of the genus Channa include several carnivorous species that possess high economic value and are widely recognized as staple food fish (Courtenay and Williams, 2004;Qin and Fast, 2007;Sampath, 1984;Sampath and Pandian, 1984;Wee, 1982). In addition, snakeheads are used as ornamental fish in aquariums and their consumption is considered therapeutic for wound healing after trauma and surgical procedures including, Cesarean sections (Benziger et al, 2011;Gam et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To date, very limited information is available on haruan nutrition (Qin & Fast 1997). In culture practices, snakeheads are commonly fed trash fish and cattle blood mixed with rice bran, wheat flour or spent grains (Wee 1982; Victor & Akpocha 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In culture practices, snakeheads are commonly fed trash fish and cattle blood mixed with rice bran, wheat flour or spent grains (Wee 1982; Victor & Akpocha 1992). Qin & Fast (1997) reported that larval snakehead accepted formulated feed from the size of 12 mm total length and larval snakehead have been weaned from feeding live Artemia unto compounded feed (Qin et al. 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Captive reproduction and larval rearing of snakehead have been accomplished experimentally, but are not done on a commercial scale [2,10]. Attempts have been made to develop rearing techniques for snakehead in Hawaii, USA [16]. During the early post larval stage, it is better to feed them with small plankton like rotifers and Artemia nauplii [6,10].…”
Section: Seed Production and Culturementioning
confidence: 99%